Digital Learning and Teaching in the Age of COVID-19 Pandemic : Challenges, Opportunities,and Solutions - Nadiah Abidin; Wahidin Septa Zahran; Trie Andari Ratna Widyastuti; Vita Vitisia; Saktisyahputra (Ilomata International Journal of Social Science, 2021)
Abstract The COVID-19 pandemic has swept the world and changed the map of education. Higher education institutions have been forced to close and hold digital learning classes to cope with governmental regulations prohibiting face-to-face interactions. This includes STIAMI Institute of Social and Management Science branch Bekasi City. With a total of 2593 students, 130 lecturers, and 60 campus administration staffs, civitas academica of Institut STIAMI Bekasi have been inevitably learning and working from home since February 2020. Such change has caused challenges and opportunities. Hence, the following paper tries to dissect students', lecturers', and campus administrations' perspectives about digital learning and teaching. The method used in the research is qualitative with case study approach, incorporating in-depth interviews and observations. Based on the results, all parties perceived full digital learning and teaching as best decision to cut the pandemic chain, although found it as a challenge and have experienced mental health and technical problems, yet found positive outcomes that lead to education without boundaries. Thus, it is recommended to hold private and group consultations; interactive workshops; local-national-international cooperations to ensure digital learning and teaching in the long run becomes bearable, productive, and beneficial for everyone involved.